Do adaptive cycles of floodplain vegetation response to inundation differ among vegetation communities?. (11th September 2019) - Thapa, Rajesh; Thoms, Martin C.; Reid, Michael; Parsons, Melissa
Abstract: Flooding is a key driver of floodplain vegetation productivity. Adaptive cycles provide a model for examining the productivity of floodplain vegetation communities in response to hydrology. Accordingly, floodplain inundation drives vegetation productivity responses through an adaptive cycle of wetting (exploitation phase), wet (conservation phase), drying (release phase), and dry (reorganization phase). We examined changes in the productivity of four floodplain vegetation communities (lignum, coolibah, grass, and poplar box) through the four phases of an adaptive cycle and explore the various strategies used by these vegetation communities to cope with variation in water availability. All four vegetation communities showed significant differences in productivity, as indicated by changes in the normalized difference vegetation index between the adaptive cycle phases. Differences were evident in the total area of vegetation that showed a productivity response, the quality or the vigour of the response, the trajectory of change overtime (i.e., towards higher or lower productivity), and the probability of change. Although the four vegetation communities exhibited response patterns in relation to flooding and drying that fit the adaptive cycle model, differences were evident in the timing of transitions between the four phases and the duration spent in those phases for each vegetation community. Poplar box and coolibah communities showed a higher productivity response during the drying or release phase. By comparison, the highest productivity response for the grassland and lignum shrubland was observed during the wetting or exploitation phase. Overall, the results showed that the four vegetation communities are sensitive to the degree of wetting at different phases in the adaptive cycle. Knowledge of floodplain vegetation response in each phase of an adaptive cycle will enable better management of floodplains, as management activities can be tailored to adaptive phase patterns associated with each community.